Lactic acid bacteria as biological control agent against papaya dieback disease - Anas, Nurul Fatihah (2015)
Papaya (Carica papaya) is an economically fruit crop grown in Malaysia. However, the outbreak of Papaya Dieback disease on papaya industry has caused a rapid declination in papaya production. The aim of the study was to isolate and identify endophytic Lactic Acid Bacteria (LAB) from papaya that able to inhibit Erwinia mallotivora, the causative agent of Papaya Dieback disease. The bacterial cultures from papaya seed extract were serially diluted and plated on M17 agar supplemented with 0.5 % glucose. 18 out of 70 colonies were tested positive to inhibit this pathogen using agar disc diffusion assay. The antibacterial activity was recorded by measuring the diameter in (mm) of clear inhibition zone surrounding the disc. The isolate A28 showed the highest clear inhibition zone which is 10 mm. The morphological characterization and biochemical test of the isolated strains indicated that they were Gram-positive, cocci shape and catalase-negative. Molecular characterization of the bacterial endophytes using 16S rRNA sequencing is still in progress. The phylogenetic analysis of 16S rRNA gene sequences will be performed. The selected microbial isolates obtained in this study will be used in controlling Papaya Dieback disease. To our knowledge, the biological approach using LAB to control this disease has not yet been applied in Malaysia.